Enhancing governance for environmental sustainability in sub-Saharan Africa - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2019)
This study assesses whether improving governance standards affects environmental quality in 44 countries in sub-Saharan Africa for the period 2000-2012. The empirical evidence is based on Generalised Method of Moments. Bundled and unbundled governance dynamics are used notably: (i) political governance (consisting of political stability and "voice & accountability"); (ii) economic governance (entailing government effectiveness and regulation quality), (iii) institutional governance (represented by the rule of law and corruption-control) and (iv) general governance (encompassing political, economic and institutional governance dynamics). The following hypotheses are tested: (i) Hypothesis 1 (Improving political governance is negatively related to CO2 emissions); (ii) Hypothesis 2 (Increasing economic governance is negatively related to CO2 emissions) and (iii) Hypothesis 3 (Enhancing institutional governance is negatively related to CO2 emissions. Results of the tested hypotheses show that: the validity of Hypothesis 3 cannot be determined based on the results; Hypothesis 2 is not valid while Hypothesis 1 is partially not valid. The main policy implication is that governance standards need to be further improved in order for government quality to generate the expected unfavorable effects on CO2 emissions.
Keywords: C52; O38; O40; O55; P37; 330; CO2 emissions; Governance; Economic development; Sustainable development; Africa